Innovations in Plant Biotechnology: Transforming Horticulture for a Sustainable Future - Shreya Singh (International Journal of Trends in Horticulture, 2024)
The increasing global demand for sustainable energy sources has intensified interest in biofuels, particularly those derived from algae. Algae-based biofuels offer a promising alternative to traditional fossil fuels due to their high lipid and oil content, rapid growth rates, and adaptability to diverse environments. This review article examines the potential of algae as a biofuel source, focusing on recent advancements in algal cultivation, lipid extraction, and biofuel production technologies. Population growth and rising standards of living worldwide are driving up energy demands, highlighting the need for diversified biofuel sources. Among these, algal biomass has garnered significant attention for its high growth rate, potential to reduce greenhouse gas (GHG) emissions, and capability to store high lipid and carbohydrate levels. These versatile organisms can also be harnessed for biofuel production. This review discusses the sustainability and viability of algae as a biofuel feedstock, offering an overview of the current status of biofuel production through algal biomass and the progress achieved in this area.
Keywords: Algaculture; Biofuels; Macroalgae; Microalgae; Oil Production; algae; biomass; sustainable energy; wastewater treatment